MEMORANDUM [REGARDING PUBLIC SMOKING] - CHILCOTE,SAMUEL (Tufts Archival Research Center, 2007)
Handwritten; Memorandum from Sam Chilcote to the Executive Committee regarding the House Energy and Commerce Subcommittee on Health and the Environment hearing on a bill virtually banning public smoking nationwide. Lists groups and individuals testifying in support of banning public smoking nationwide. Outlines industry preparation for the hearing including testimony from Gray Robertson, director of the Beverly Hills Restaurant Association, industry scientists and smokers’ rights advocates.